The Influence of Microclimatic Ammonia Changes in Closed House on Broiler’s Performance in Dry Season - Angkeke, Ica Putri; Sarjana, Teysar Adi; Suprijatna, Edjeng (ANIMAL PRODUCTION, 2018)
This research aims at investigating the impact of microclimatic ammonia change on Broiler’s  performance in closed house during dry season. Seven hundred and twenty broiler’s with their initial weight of 49.29 ± 1.13 grams are kept in a 60 x 12 m2 cage.The research consists of 4 treatments and 6 experiment units. The microclimatic ammonia change is measured at a distance of 0, ¼, ½, and ¾ of closed house’s length from the inlet. The parameters observed are feed consumption, body weight gain (BWG), feed convertion ratio (FCR), performance index (PI) and Income Over Feed Cost (IOFC). The obtained data are subjected to analysis of variance and several data related to microclimatic ammonia and heat stress index (HSI) are also calculted for their correlation to find out their correlation with the broiler’s’s performance. The research results indicate that the microclimatic ammonia change significantly reduces Broiler’s performance. This is shown by the significant increase of FCR value, decrease of feed consumption, BWG, PI and IOFC (P≤0.05) starting from a distance of ¼ of cage length from the inlet. The correlation analysis result shows a negative, significant correlation between performance with ammonia, while HSI does not show any correlation with the observed parameters. The conclusion of this research is that the increase in microclimatic ammonia at increasingly further distance from the inlet decreases Broiler’s  performance in dry season.